EFFECT OF BRAND AND MARKET PERFORMANCE ON COMPETITIVENESS IN MERGERS AND ACQUISITIONS - AYAR, BAHADIR; AYDOĞAN, SİBEL (FUTURE ACAD, 2019)
Today's intense global competition conditions have led the local and small markets to leave their places to bigger and more developed markets. In addition to this, businesses have to make different strategic decisions in order to survive and profit. One of the ways for firms that fail to increase their brand equity with their own resources is to go through a merger and / or acquisition transaction with a different firm. In this way, firms which benefit from each other's strengths are striving to exist, differentiate and grow in an international competitive environment with the impact of globalization. The main purpose of this research is the effect of market and brand performance on competitiveness in the context of mergers and acquisitions transactions which are done in Turkey. The universe of the study is the firms that have performed mergers and acquisitions transactions in Turkey. Between 2010 and 2017, 2287 firms that have performed mergers and acquisitions transactions constitute the sample framework of the study and the sample size is limited to 243 enterprises. As a result of the analyses, the current status of the effect of brand performance on competitiveness according to our findings has been evaluated, and new proposals regarding this topic have been made for future researches. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Merger; acquisition; brand performance; market performance; competitiveness; STRATEGY; CHAIN